Сто великих мастеров прозы - Грудкина Татьяна Владимировна (100 великих, 2007)
Экземпляры: ф.23 (2008) / Инвентарный номер: 52217 / Цена: / Сис.шифр: 83.3 / Авт.знак: С 81 / ГРНТИ: 17.09 / ББК: 83.3(0)z2